Cardiac magnetic resonance imaging in arrhythmogenic cardiomyopathy: evolving diagnostic criteria and new capabilities - S A. Aleksandrova; E. Yu. Glazkova; E. Z. Golukhova (Российский кардиологический журнал, 2024)
In the updated diagnostic criteria for arrhythmogenic cardiomyopathy (ACM) (2020 and 2022), magnetic resonance imaging (MRI) has become the preferred method for cardiac imaging. This is due to advances in MRI and the accumulation of evidence on its reliability. Non-invasive assessment of myocardial fibrotic replacement using late gadolinium enhancement techniques is a key innovation, which, along with histology data, was included in the category of "structural changes". The technique has demonstrated significance in identifying various ACM phenotypes (primarily the left ventricular one), in differential diagnostics and family screening of the disease. The relevance of MRI data has been proven in predicting the risks of adverse cardiovascular events, including sudden cardiac death. Some MRI techniques, such as T1 mapping and myocardial strain assessment, are under study, but they have already shown promise in studies on small groups. Obtaining and interpreting cardiac MRI data in patients with ACM requires not only standardized protocols and high experience of a radiologist, but also teamwork with cardiologists. The article summarizes the current capabilities of MRI in ACM and provides a practical approach to diagnosis and risk stratification.